The pretender's gambit - Archer, Alex (Archer, Alex. Rogue angel., 2014)
Called in by the NYPD to investigate a murder and the disappearance of a priceless artifact that once belonged to Catherine the Great, archaeologist Annja Creed must work quickly to find it before it falls into the hands of a cruel mogul with a penchant for tomb-raiding - and murder.